488 Falls and physical activity in older Australian women from two different generations. (20th November 2022) - Kwok, Wing; Dolja-Gore, Xenia; Khalatbari-Soltani, Saman; Byles, Julie; Pinheiro, Marina; Oliveira, Juliana; Sherrington, Catherine
Abstract : Background: Falls, injurious falls, and physical activity (PA) could be different between different generations. The Australian Longitudinal Study on Women's Health provides an opportunity to explore the associations between PA and falls and injurious falls in older women with similar ages of different generations. Methods: The sample involved 8311 women born 1921–26 (mean (SD) age: 75 (1) years, 1999 survey) and 7540 women born 1946–51 (71 (1) years, 2019 survey). Falls, injurious falls and any PA participation were reported. The cohorts' differences in falls, injurious falls and PA participation were examined using Chi-square test. The association between PA participation and falls and injurious falls was estimated in odds ratios (ORs) with 95% confidence intervals (CIs), using multivariable multinominal logistic regression with adjustment for confounders. Results: Compared to the 1921–26 cohort, a greater proportion in the 1946–51 cohort had some PA participation (83% versus 68%, p<0.001) and had fallen without injuries (14% versus 8%, p<0.001). However, both cohorts had similar proportions of injurious falls (1946–51:15%; 1921–26:14%, p=0.11). In both cohorts, any PA was associated with lower risk of falls compared to no PA participation (OR1921–26:0.75(95%CI 0.64–0.89); OR1946–51:0.82(95%CI 0.69–0.97)) and injurious falls (OR1921–26:0.74(95%CI 0.64–0.84); OR1946–51: 0.72(95%CI 0.61–0.84)). Conclusion: While the 1946–51 cohort has a higher fall without injuries prevalence than 1921–26, both cohorts had similar injurious falls prevalence. PA participation was associated with lower risk of falls and injurious falls in both cohorts. Learning outcomes: Having any PA participation was associated with lower falls risk and injurious falls.